DETAIL ENGINEERING DESIGN INFRASTRUKTUR TEKNOLOGI INFORMASI PERINGATAN DINI BANJIR DINAS PENGAIRAN PROVINSI ACEH - Said Bambang Nurcahya; Nana Sujana; Nur Azizah (LPPM Politeknik Pajajaran ICB Bandung, 2022)
The complexity of life in the world is the most difficult to anticipate when natural phenomena occur in the form of rain, earthquakes, landslides, volcanic eruptions, and whirlwinds. The natural event that causes an area to become a natural disaster most often is flooding, basically the rain that occurs can be predicted in terms of intensity, rainfall, volume, and time of occurrence. BMKG as a government institution that researches natural phenomena usually provides daily weather forecasts and the information can be obtained on websites and online media, TV, social media and other media, the Nangroe Aceh Darussalam Provincial Irrigation Service which is responsible for planning, handling, and construction of irrigation and The use of irrigation is challenged to make innovations using information technology and incorporating technically designed hardware telemetry (DED) to combine it into a flood early warning system, especially in river flows close to residential areas so that it can anticipate or mitigate flood disasters massively and informatively. to local governments, communities, media and other parties with an interest in the main tasks and functions of rescue. In developing and combining hardware, software, and brainware for this flood early warning system, the main focus was the use of Hawk Eye, high resolution CCTV operated using Igismap software, and Dynamic software, which successfully identified garbage in rivers that caused puddles, and sent signals and data to the Command Center (EWS Command Center).